Effect Of Polar Component(1-Propanol) On The Relative Volatility Of The Binary System N-Hexane - Benzene - Chasib Al-Jiboury, Khalid Farhod (Al-Khwarizmi Engineering Journal, 2008)
Vapor-liquid equilibrium data are presented for the binary systems n-hexane - 1-propanol, benzene - 1-propanol and n-hexane – benzene at 760 mm of mercury pressure. In addition ternary data are presented at selected compositions with respect to the 1-propanol in the 1-propanol, benzene, n-hexane system at 760 mmHg. The results indicate the relative volatility of n-hexane relative to benzene increases appreciably with addition of 1-propanol.